Porous shroud tube design evaluation of a control plug in a liquid metal cooled reactor. (5th July 2018) - Gautam, Ankit Kumar; Kumar, Sunil; Panigrahi, Pradipta Kumar
Highlights: Lower free surface turbulence at higher free surface height of shroud tube. Amplification of hump instability due to eccentricity of control rod. Gas entrainment initiation at low Froude number for small shroud tube pore size. Lower radial velocity through pores for higher shroud tube thickness. Abstract: Shroud tube is a porous protective covering over the Control Safety Rod Driving Mechanism assembly vertically submerged just below the free-surface of liquid sodium coolant pool of a Fast Breeder Reactor. Pore size and its arrangement over the shroud tube are important design parameters, which influence the gas entrainment and flow induced vibration inside the liquid coolant pool leading to several reactor operation related risks. The present study focuses on performance evaluation of three shroud tube designs of same porosity but with different pore diameter, thickness of shroud tube and arrangement of pores (staggered and uniform). A parametric investigation with respect to parameters viz. Froude number, free-surface height, and the eccentricity of the control rod has been carried out using white light imaging and high speed laser based Shadowgraphy. The present study effectively demonstrates the complexity in design of porous shroud tube and the role played by several design parameters. The radial flow from the pores and its interaction with the downward flow due to hump motion influence the air-water interface dynamics which influences the gas entrainment process. The flow induced fluctuation of the hump increases with increase in eccentricity of the control rod.